ANALISIS KEMAMPUAN BERPIKIR KRITIS DAN KOMUNIKASI MATEMATIS SISWA DALAM PEMECAHAN MASALAH MATEMATIKA BERTIPE SOAL TIMSS - Sukma Dwi Febriyanti; Intan Indiati; Rina Dwi Setyawati (Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2022)
This study aims to describe students' critical thinking and mathematical communication skills Algebra material TIMSS type of question. This type of research is descriptive qualitative. The subjects were taken by 3 students each with high, medium and low math abilities in class VIII of SMPN 1 Jepara 2021/2022. Data was collected by means of critical thinking tests, mathematical communication, interviews and documentation. The data analysis technique was carried out in 3 stages, namely data reduction, data presentation and conclusion drawing. The technique of checking the validity of the data is using the triangulation method. Critical thinking analysis, 1 student with high mathematical ability who fulfills all indicators while the other 2 students only meet 2 critical thinking indicators. Students with moderate mathematical ability 3 students who are only able to fulfill 1 indicator of critical thinking. Students with low mathematical abilities, 1 student who is only able to fulfill 1 indicator while the other 2 students are not able to fulfill all critical thinking indicators. For mathematical communication, students with high mathematical ability met 5 indicators of mathematical communication, 2 students with moderate mathematical ability met 3 indicators but the indicators achieved were different while 1 other student met 4 indicators of mathematical communication. 2 students with low mathematical ability met 1 indicator and 1 other student was not able to fulfill all mathematical communication indicators.